Characterization of Neofabraea vagabunda isolates causing apple bull's eye rot in Italy (Emilia‐Romagna region). (6th March 2017) - Cameldi, I.; Neri, F.; Menghini, M.; Pirondi, A.; Nanni, I. M.; Collina, M.; Mari, M.
Abstract : Neofabraea vagabunda is the prevalent cause of bull's eye rot, one of the main postharvest diseases of apple, in many producing areas, but its biology has not been studied in detail. The molecular identification, by DNA sequencing of the β ‐tubulin region, of 41 isolates collected from apples showing bull's eye rot in the Emilia‐Romagna region confirmed N. vagabunda as the main species in Italy. A biological and morphological characterization of N. vagabunda isolates was performed in vitro . Assays at temperatures ranging from 0 to 30 °C carried out on 10 isolates demonstrated: (i) a marked influence of temperature on colony morphology, conidial production, conidial size and mycelial growth, showing the cold‐tolerant character of N. vagabunda ; and (ii) that culture at 15 °C on tomato agar (TA) for 14 days is a rapid and reliable method to favour pathogen conidial production. Trials performed on 38 isolates using these incubation conditions recorded the presence of two N. vagabunda morphotypes, differing for colony morphology, conidial size, conidiomata formation and temperature requirement. The alkalizing ability of the pathogen during growth on TA was also demonstrated for the first time. The pathogenicity of 25 N. vagabunda isolates was proved in vivo on artificially infected Cripps Pink apples. A pH increase was also recorded in apple tissue infected by N. vagabunda isolates (on average 0.2 and 0.3 units of pH after 60 and 120 days of incubation, respectively), suggesting that the N. vagabunda transition from quiescence to necrotrophic colonization in apples could involve the secretion of alkalizing compounds.